Pengaruh Kesadaran, Penyuluhan, Pelayanan, dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi (Studi di Kantor Pelayanan Pajak Pratama Malang Selatan) - Lalu Perdana Anugrah Hasyim; Moh. Amin; Afifudin Afifudin (Universitas Islam Malang, 2023)
The research utilizes a quantitative approach to examine the impact of taxpayer awareness, tax education, tax services, and tax sanctions on individual taxpayer compliance. The variables explored include taxpayer awareness, tax education, tax services, and tax sanctions as independent variables, with compliance being the dependent variable. The research sample comprises 100 individual taxpayers registered at KPP Pratama Malang Selatan. A questionnaire is employed as the data collection instrument, and the SPSS 25.0 computer program is utilized to conduct the instrument test. The data is analyzed through multiple linear regression analysis, traditional assumption tests, determination tests, F tests, and t tests. The research findings reveal that compliance, tax services, and tax sanctions have a significantly positive impact on individual taxpayer compliance, while tax education does not exhibit a significant effect on individual taxpayer compliance.Keywords: Taxpayer awareness, tax education, tax services, and tax sanctions on the compliance of individual taxpayers.